Pengaruh Motivasi dan Metode Pembelajaran Terhadap Prestasi Belajar Mahasiswa Akuntansi Semester IV Tahun Ajaran 2024-2025 - Wangko, Lukman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Student success in learning is influenced by several factors, one of which is the method used by lecturers in teaching. In reality, conventional methods are still used in learning, so students are less active in learning and their learning achievement is less than satisfactory. Students can achieve maximum learning achievement if a lecturer is right in applying the teaching method. For this reason, an innovative learning method is needed that is able to increase student activity and learning achievement, namely the peer tutor method in small groups. From this, the problem arises, namely how effective is the application of the peer tutor method in small groups to improve accounting learning achievement. The population in this study were all fourth semester students of the Accounting Study Program, Faculty of Economics, Pacific University, academic year 2003/2024, totaling 52 students divided into 2 classes. The sample was determined using a simple random sampling technique, namely classes A and B totaling 52 students. The data collection techniques used were documentation techniques and experimental techniques. While the data collection tool used a test. In this study, there were 2 data analyzes, namely initial data analysis to match the experimental group and the control group using the normality test, the two variance equality test and the two mean equality test, and the final stage analysis to test the hypothesis with the t-test formula (Independent Sample). The results of the study obtained t count = 2.186, while t table = 1.99 with a = 5% and df = 39 + 39 = 78. So t count t table so that the hypothesis is accepted. The results of the t-test analysis show that the average learning achievement value obtained by the experimental group is better than the average learning achievement value obtained by the control group. Thus, it can be concluded that the application of peer tutoring as a learning method for accounting, the main topic of special journals for trading companies, is more effective than conventional methods.